Evidence of the Mechanism by Which Polyomaviruses Exploit the Extracellular Vesicle Delivery System during Infection - Giannecchini, Simone (Viruses, 2020)
Increasing evidence suggests that human viruses can hijack extracellular vesicles (EVs) to deliver proteins, mRNAs, microRNAs (miRNAs) and whole viral particles during viral persistence in the host. Human polyomavirus (PyV) miRNAs, which downregulate large T-antigen expression and target host factors, help the virus escape immune elimination and may have roles in the success of viral persistence/replication and the development of diseases. In this context, several investigations have detected PyV miRNAs in EVs obtained from cell culture supernatants after viral infection, demonstrating the ability of these vesicles to deliver miRNAs to uninfected cells, potentially counteracting new viral infection. Additionally, PyV miRNAs have been identified in EVs derived from the biological fluids of clinical samples obtained from patients with or at risk of severe PyV-associated diseases and from asymptomatic control healthy subjects. Interestingly, PyV miRNAs were found to be circulating in blood, urine, cerebrospinal fluid, and saliva samples from patients despite their PyV DNA status. Recently, the association between EVs and PyV viral particles was reported, demonstrating the ability of PyV viral particles to enter the cell without natural receptor-mediated entry and evade antibody-mediated neutralization or to be neutralized at a step different from that of the neutralization of naked whole viral particles. All these data point toward a potential role of the association between PyVs with EVs in viral persistence, suggesting that further work to define the implication of this interaction in viral reactivation is warranted.